Reliability Improvement of RF Identification of Shadowed People in Building Corridors Using Space Diversity - M. Svanda; M. Kvicera; M. Polivka (Radioengineering, 2018)
This paper deals with the investigation of space diversity techniques for elimination of signal fading and consequently extension of coverage area in applications of RF identification of shadowed people in a building corridor. Several measurement scenarios were evaluated. They comprised up to four wearable tags placed at different positions on a human body with one or two reader antennas, including shadowing by a small crowd of people. It was shown that the achieved corresponding SIMO mode diversity gain accounted for ca. 1 dB at the overall improvement in the trace coverage amounted to ca. 5%. On the other hand, the MIMO mode diversity configuration brought an improvement of up to 10% and enabled to cover more than 50% of the identification area, including the scenario where shadowing by a small crowd of people was present.